2023
DOI: 10.1002/adfm.202301755
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Charging of a 4.8 V Manganese‐Rich Cathode‐Based Lithium Metal Cell by Constructing Robust Solid Electrolyte Interphases

Abstract: Fast charging of Li-metal battery (LMB) is a challenging issue owing to the interfacial instability of Li-metal anode in liquid electrolyte and Li-dendrites growth, resulting in fire hazard. Those issues motivated to pioneer a stabilization strategy of liquid electrolyte-derived solid electrolyte interphase (SEI) layer that enables dendrites-free Li-metal anode under extremely high current density, which solid-state battery cannot. Here, the novel electrolyte formulation is reported including trace-level penta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…10–12 In response to these challenges associated with LEs, researchers have explored various strategies. Significant efforts have been dedicated to optimizing electrolyte formulations, 13,14 developing solid-state electrolytes, 15–18 and designing electrolyte/electrode interfaces. 3,19 Solid electrolytes encompass inorganic solid electrolytes (ISEs) and gel polymer electrolytes (GPEs).…”
Section: Introductionmentioning
confidence: 99%
“…10–12 In response to these challenges associated with LEs, researchers have explored various strategies. Significant efforts have been dedicated to optimizing electrolyte formulations, 13,14 developing solid-state electrolytes, 15–18 and designing electrolyte/electrode interfaces. 3,19 Solid electrolytes encompass inorganic solid electrolytes (ISEs) and gel polymer electrolytes (GPEs).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the strategies put forth to solve the aforementioned challenges faced by LMBs indicate that the most viable approach to fulfilling the interfacial needs between electrolyte and electrodes, while considering manufacturing processes, cost-effectiveness, and significant impact, is the development of highly efficient functional electrolyte additives. It is widely acknowledged that the presence of LiF, an inorganic component, has shown positive effects in enhancing mechanical strength, ionic conductivity, and electronic insulation of CEI and SEI films due to its unique properties of high surface energy, large bandgap, and low Li + diffusion barrier. Accordingly, electrolyte additives with higher degree of fluorinated functional group can better generate LiF ingredient to improve the mechanical strength of CEI/SEI films and guide homogeneous Li deposition. On the basis of this knowledge, efforts have been made to enrich the types of functional electrolyte additive with F-rich groups. Song et al reported a novel pentafluoropropionic anhydride additive containing F atoms to create SEI layers enriched with fluorides and organics, which has proven highly effective in safeguarding against the growth of Li dendrites on LMA, thus delivering exceptionally high-performance Li/Mn-rich batteries over a prolonged 400 cycles . Fan et al designed an all-fluorinated electrolyte that enables the construction of several-nanometer-thick, high-LiF interphases with strong mechanical strength and high interface energy to accommodate a considerable shift in electrode volume, ultimately enabling the performance of Li/NCM811 batteries to rise dramatically .…”
Section: Introductionmentioning
confidence: 99%
“…36−38 Song et al reported a novel pentafluoropropionic anhydride additive containing F atoms to create SEI layers enriched with fluorides and organics, which has proven highly effective in safeguarding against the growth of Li dendrites on LMA, thus delivering exceptionally high-performance Li/Mn-rich batteries over a prolonged 400 cycles. 39 Fan et al designed an all-fluorinated electrolyte that enables the construction of several-nanometerthick, high-LiF interphases with strong mechanical strength and high interface energy to accommodate a considerable shift in electrode volume, ultimately enabling the performance of Li/NCM811 batteries to rise dramatically. 40 Therefore, further investigation needs to be done to explore appropriate electrolyte additives with an emphasis on developing efficient CEI/SEI films rich in LiF to achieve stable operation of highenergy density LMBs in conjunction with a Ni-rich electrode.…”
Section: Introductionmentioning
confidence: 99%